Penerapan Aromaterapi Mawar Untuk Menurunkan Tekanan Darah Pada Pasien Hipertensi - Duha, Filimbarasi; Yan, Loriza Sati; Ernawati, Ernawati (Yayasan Jompa Research and Development, 2025)
This case study aims to determine the effectiveness of nursing care using rose aromatherapy to lower blood pressure in hypertensive patients at the Kasang Pudak Community Health Center in Muaro Jambi Regency in 2025. The method used is a descriptive case study, with two hypertensive patients as subjects. The results of the 7-day case study showed that both subjects experienced a decrease in blood pressure. Routine application of rose aromatherapy to the community, especially for hypertensive patients, is effective in lowering blood pressure. Keywords: rose aromatherapy, nursing care, blood pressure, hypertensi